Β-Cyclodextrin grafted on alkali lignin as a dispersant for coal water slurry. Issue 14 (18th July 2019) - Lu, H.-Y.; Li, X.-F.; Zhang, C.-Q.; Li, W.-H.; Xu, D.-P.
ABSTRACT: A modified alkali lignin (AL) was synthesized by introducing β-cyclodextrin (β-CD) into AL with epichlorohydrin (EPI) copolymerization, which resulted in incorporating β-CD with AL by ether linkage. As a dispersant, β-CD copolymerized AL (β-CD-AL) was added into coal water slurry and its efficiency was evaluated. The effects of β-CD content on the performance of β-CD-AL were investigated via analyzing dispersity, zeta potential, and adsorption capacity. The results illustrated that β-CD-AL behaved better dispersion owing to the high slurry concentration at fixed apparent viscosity, which was mainly attributed to the synergistic effects of electrostatic repulsive force and steric hindrance. Steric hindrance originated from the side chain of β-CD gives better stability and less adsorption amount.